Evaluation of burnout levels among healthcare staff in anesthesiology departments in Greece - Is there a connection with anxiety and depression? - Aikaterini Toska; Sofia Ralli; Evangelos C. Fradelos; Ioanna Dimitriadou; Anastasios Christakis; Viktor Vus; Maria Saridi (AIMS Press, 2024)
Introduction Healthcare workers in anesthesiology departments often experience burnout syndrome, which may be combined with anxiety and depression. Aim The study aimed to assess the levels of burnout among nurses and physicians working in anesthesiology departments in public hospitals in Attica and to investigate a possible correlation between burnout, anxiety, and depression. Methodology A cross-sectional study was conducted on physicians and nurses working in anesthesiology departments in public hospitals in Attica, Greece. A questionnaire was distributed electronically using the snowball sampling method, including questions about demographic characteristics, burnout, anxiety, and depression. Results Physicians and nurses in anesthesiology departments were found to have moderate levels of burnout, and normal/low levels of anxiety and depression. More specifically, it was found that 2% of physicians and 14.4% of nurses had extremely elevated levels of burnout. On the other hand, 6.1% of physicians and 23.7% of nurses had high anxiety, while 6.1% of physicians and 15.5% of nurses had elevated levels of depression. Females (p = 0.008), staff aged 45-55 (p = 0.021), lower educational level (p = 0.025), nurses (p = 0.001), more than 21 years of service (p = 0.001), and having children (p = 0.008) were determinants of greater levels of personal burnout. Work-related burnout correlated with having children (p = 0.017), whereas client-related burnout was significantly higher for nurses (p = 0.002). In addition, a correlation was found between anxiety, depression, and increased levels of burnout (p = 0.000). Conclusions As physicians and nurses working in anesthesiology departments have stressful jobs and work long hours, it is important to further study their physical, emotional, and mental exhaustion as well as psychological resilience levels.